Service Condition of Customer Service Inhealth Admision RSUP Dr. Mohammad Hoesin Palembang when Serves BPJS Patient in 2014 - Alphiano, K M Dimas; Zulkarnain, M; Syakurah, Rizma Adlia (Medicinus, 2019)
Introduction : Health Service includes administrative service. In RSUP Dr. Mohammad Hoesin Palembang, it is implemented by Customer Service Inhealth Admision. To describe the service condition of Customer Service Inhealth Admision when serves BPJS patients in 2014 based on the quality of service which are reliability, responsiveness, emphaty, tangible, and assurance and how it actualized them, it is necessary in depth interview and observation in Customer Service Inhealth Admision RSUP Dr. Mohammad Hoesin Palembang.Method : This study used observation and in depth interview with respondents, which were chosen purposively. The data were then transcribed and analysed for themes using deductive content analysis.Result : Service condition of Customer Service Inhealth Admision RSUP Dr. Mohammad Hoesin Palembang in 2014 is the service condition which are reliable and responsive, making efforts to actualize emphaty, tangible, and assurance aspects when serves the patients either BPJS or general before they hospitalized in RSUP Dr. Mohammad Hoesin Palembang.Conclusion : Customer Service Inhealth Admision requires improvement, in particular the queue system for the patients who want to find their bed before they hospitalized. Employee of Customer Service Inhealth Admision should enhance their efforts to actualize emphaty and assurance aspects when serve the patients.